Story of Naani Goo, appellation of Naa Andani - Lunna, Abubakari; Locke, David (Tufts Archival Research Center, 2005)
Told by Abubakari Lunna on March 2 and 6, 2001. Edited by David Locke. Describes the origins of the Naani Goo rhythm that tells the story of how Naa Andani became chief.